AN ANALYSIS OF THE REPRESENTATION OF FEMALE MEMBERS OF THE UNITED KINGDOM PARLIAMENT IN THE BRITISH PRESS - Insenga, Michela (European Scientific Journal, ESJ, 2014)
This study analyses the media discourse of the British press on female politicians in the UK deconstructing the language used to depict them as political candidates, aiming at identifying recurrent patterns and stereotypical frameworks. Main aim of this research is to argue that the media discourse plays against the targets set by the Europe2020 strategies to achieve gender equality, perpetuating gendered media constructions of women. To carry out this research project, the newspapers have been chosen with mind to a balance between broadsheets and tabloids from the conservative and liberal side. A mixed methodology of content analysis and some framing mechanisms has been used to test the argument. Findings suggest that the British press depict female politicians through a number of stereotypical frameworks that involve physical appearance, emotional status, their family role as mothers or wives, or their association to the so-called ’compassion issues’. Although there are evidence of differences due to affiliation to different parties, or to different political roles, the UK newspaper media actively – although it cannot be said whether this is consciously or subconsciously – re-attaches women political leaders to communal gender stereotypes, ensuring that the public are reminded that a female political leader is ‗always a woman, sometimes a politician‘.